2011
DOI: 10.1016/j.compstruc.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and vibration analysis of laminated composite plate/shell structures via a smoothed quadrilateral flat shell element with in-plane rotations

Abstract: This paper presents buckling and free vibration analysis of composite plate/shell structures of various shapes, modulus ratios, span-to-thickness ratios, boundary conditions and lay-up sequences via a novel smoothed quadrilateral flat element. The element is developed by incorporating a strain smoothing technique into a flat shell approach. As a result, the evaluation of membrane, bending and geometric stiffness matrices are based on integration along the boundary of smoothing elements, which leads to accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…We consider the normalized critical buckling load factors of SSSS, SSFF, SSCC, SSFC, and SSFS plates with length‐to‐thickness ratios of a ∕ h = 10 and modulus ratios of E 1 ∕ E 2 = 40. Given as in Table , the results of the present method agrees well with the solution of several other methods such as MISQ20 , MLSDQ , the reproducing kernel particle method (RKPM) and the finite element method based on FSDT and HSDT . Figure illustrates buckling shape modes of 10‐layer [0° ∕ 90°] 5 plate with various boundary conditions.…”
Section: Numerical Resultssupporting
confidence: 75%
“…We consider the normalized critical buckling load factors of SSSS, SSFF, SSCC, SSFC, and SSFS plates with length‐to‐thickness ratios of a ∕ h = 10 and modulus ratios of E 1 ∕ E 2 = 40. Given as in Table , the results of the present method agrees well with the solution of several other methods such as MISQ20 , MLSDQ , the reproducing kernel particle method (RKPM) and the finite element method based on FSDT and HSDT . Figure illustrates buckling shape modes of 10‐layer [0° ∕ 90°] 5 plate with various boundary conditions.…”
Section: Numerical Resultssupporting
confidence: 75%
“…It is found that with refining meshes, results obtained by the present FE model converge closely to the exact solution [26] and reasonably close to the 3D elasticity solution given by Noor [13]. The present finite element model based on higher order zigzag theory gives the more accurate results compared to the results given by Fiedler et al [33] based on a similar theory, results of Van et al [25] based on first order shear deformation theory and results of Ferreira et al [10] based on first order shear deformation theory respectively. Some new results are also presented in Table 2.…”
Section: Cross-ply Multilayered (0/90/) Composite Plate Simply Suppsupporting
confidence: 33%
“…The material properties are same as in section 3.2 where E 1 /E 2 is taken as 40. The results obtained by the present finite element model are shown in Table 4 along with those obtained by Van et al [25], Reddy and Phan [27], and Chakrabarti and Sheikh [31] respectively. The same trend as explained before is also observed in the results presented in Table 4.…”
Section: Cross-ply Multilayered (0/90/) Composite Plate Simply Suppmentioning
confidence: 68%
See 1 more Smart Citation
“…This paper presents a novel numerical procedure based on four-node element MISQ24 with inplane rotations [6] associated with the C 0 -HSDT type for static and free vibration analyses of laminated composite plates. The higher-order shear deformation plate theory is involved in the formulation in order to avoid using the shear correction factors and to improve the accuracy of transverse shear stresses.…”
Section: Introductionmentioning
confidence: 99%